Navigating challenges and opportunities: AI’s contribution to Pakistan’s sustainable development goals agenda – a narrative review - Abhishek Lal; Fahad Umer (Journal of the Pakistan Medical Association, 2024)
Sustainable Developmental Goals (SDGs) were introduced by the United Nations to ensure the sustainable progress of mankind through various domains. Pakistan, a low-middle-income country, faces many challenges in achieving SDGs. Artificial Intelligence is a rapidly evolving technology presenting significant importance in achieving SDGs. Therefore, this narrative review aimed to evaluate the artificial intelligence technologies that have been utilized globally and nationally which can be implemented in Pakistan focusing on Goal 3 (Good Health and Well-being) of SDGs. AI has been utilized primarily in high-income countries aiming to improve healthcare, thereby progressing towards achieving different targets of Goal 3 of SDGs. Pakistan lacks such initiatives with modest to no improvement across different SDGs. Therefore, Pakistan can adapt initiatives undertaken by resourceful countries to achieve its own SDGs. Keywords: Sustainable Development, Goals, Artificial Intelligence, Health Care, Technology.